Light-induced in situ chemical activation of a fluorescent probe for monitoring intracellular G-quadruplex structures. Issue 32 (4th August 2021) - Deiana, Marco; Mosser, Maëlle; Le Bahers, Tangui; Dumont, Elise; Dudek, Marta; Denis-Quanquin, Sandrine; Sabouri, Nasim; Andraud, Chantal; Matczyszyn, Katarzyna; Monnereau, Cyrille; Guy, Laure
Abstract : A photochemically generated fluorophore is used to monitor intracellular G-quadruplex structures. Abstract : Light-activated functional materials capable of remote control over duplex and G-quadruplex (G4) nucleic acids formation at the cellular level are still very rare. Herein, we report on the photoinduced macrocyclisation of a helicenoid quinoline derivative of binaphthol that selectively provides easy access to an unprecedented class of extended heteroaromatic structures with remarkable photophysical and DNA/RNA binding properties. Thus, while the native bisquinoline precursor shows no DNA binding activity, the new in situ photochemically generated probe features high association constants to DNA and RNA G4s. The latter inhibits DNA synthesis by selectively stabilizing G4 structures associated with oncogenic promoters and telomere repeat units. Finally, the light sensitive compound is capable of in cellulo photoconversion, localizes primarily in the G4-rich sites of cancer cells, competes with a well-known G4 binder and shows a clear nuclear co-localization with the quadruplex specific antibody BG4. This work provides a benchmark for the future design and development of a brand-new generation of light-activated target-selective G4-binders.